A Brief Review Self Nanoemulsifying Mouth Dissolving Film: Formulation and Applications in Herbal Medicine - Lusi Nurdianti (Journal of Global Pharma Technology, 2019)
The use of herbal medicines is increasing, because of the belief that natural medicines have fewer side effects than synthetic drugs. But many herbal products show low therapeutic action due to problems with solubility and improper molecular size which have an impact on low bioavailability despite having good potential. The development of self nanoemulsion (spontaneous nanoemulsion) in fast-dissolving intraoral film preparations is one alternative formulation that can be used, to improve the limitations of bioavailability and increase patient acceptance and compliance because the application of developments is effortless, given through the oral cavity, so that direct absorption occurs in the cavity mouth and enter the systemic circulation without experiencing the effects of the first cross metabolism. This study aims to explain the concepts and techniques of self nanoemulsion formulation in intraoral (mouth dissolving film) preparations to increase the bioavailability of natural active compounds in extracts with low solubility in water and their characterization and evaluation.Keyworlds: Self nanoemulsifying, Mouth dissolving fim, Herbal medicine, Bioavailability.